Digital Technology Management Challenges in Marketing Local Farm Products in Developing Countries: Analysis of International Publication Findings - Abdul Samad Arief; Seprianti Eka Putri; Amat Suroso; Abdul Wahab Syakhrani; Noor Rahmini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The success of marketing all business products is closely related to how to overcome marketing obstacles. One is the use of digital tools. In other words, there are many challenges that digital marketing tools can identify and solve. For this reason, the researchers have studied data from many international publication journals that discuss the study of marketing agricultural products in various contexts. Furthermore, the researchers examine by involving a data analysis system, rigorous evaluation of the data, and extracting the digests relevant to the formulation of this study's questions. Based on the discussion of the study data, the researchers believe that our findings are valid and reliable. The researchers succeeded in identifying the challenges of marketing agricultural products in developing countries, including the crisis of human resources operating digitally, so that they are often wrong in marketing applications, are reluctant to innovate, and lack professional marketing ideas. Hopefully, the results of this digital marketing study will be helpful for many further studies. Keywords: Digital Marketing, Agricultural Products, Management Challenges